Diagnostics in Late Periprosthetic Infections-Challenges and Solutions - Florian Hubert Sax; Marius Hoyka; Benedikt Paul Blersch; Bernd Fink (MDPI AG, 2024)
The rising number of arthroplasties is combined with a rising number of periprosthetic joint infections, which leads to life-concerning consequences for the patients, including extended antibiotic treatment, further surgery and increased mortality. The heterogeneity of the symptoms and inflammatory response of the patients due to, e.g., age and comorbidities and the absence of a single diagnostic test with 100% accuracy make it very challenging to choose the right parameters to confirm or deny a periprosthetic joint infection and to establish a standardized definition. In recent years, additional diagnostic possibilities have emerged primarily through the increasing availability of new diagnostic methods, such as genetic techniques. The aim of the review is to provide an overview of the current state of knowledge about the various tests, including the latest developments. The combination of different tests increases the accuracy of the diagnosis. Each physician or clinical department must select the tests from the available methods that can be best implemented for them in organizational and technical terms. Serological parameters and the cultivation of the samples from aspiration or biopsy should be combined with additional synovial tests to create an accurate figure for the failure of the prosthesis, while imaging procedures are used to obtain additional information for the planned therapeutic procedure.